Virological response and predictive factors for antiviral treatment in chronic HBV-related liver disease with low ALT and high HBV DNA - Ma, Lei; Li, Yan; Weng, Lihan; Xing, Huichun (Frontiers in Immunology, 2025)
ObjectiveTo investigate virological response and predictive factors for antiviral treatment in chronic HBV patients with low ALT and high HBV DNA.MethodsA retrospective study grouped chronic HBV patients by baseline ALT: ALT > 80 U/L (significantly elevated group, SAG), 40-80 U/L (mildly elevated group, MAG), and ≤ 40 U/L (normal group, NG). Inverse probability treatment weighting balanced confounding factors. Complete virological response (CVR, HBV DNA < 20 IU/mL) and partial virological response (PVR, HBV DNA ≥ 20 IU/mL) were defined. NG subgroup analyses were performed using baseline ALT (cutoff: 30 U/L for males, 19 U/L for females), HBV DNA (cutoff: 7.21 Log10 IU/mL), and Aspartate Aminotransferase to Platelet Ratio Index (cutoff: 0.32). Cox regression identified factors predicting CVR at week 48.ResultsAfter IPTW, the number of patients in the NG, MAG, and SAG groups was 92, 141, and 284, and the CVR rates at week 48 were 38.05%, 55.26%, and 7analyses 3.32% respectively (p < 0.0001). Weighted Kaplan-Meier analysis showed that the NG group had the lowest probability of achieving CVR at week 48 (p < 0.0001). Particularly, in the NG group, the high-normal ALT subgroup had a higher CVR rate (56.34% (40/71)) than the low-normal ALT subgroup (29.73% (11/37), p = 0.0103), similar to that of the MAG group (p = 0.9871). The low-HBV DNA (82.46% (47/57)) and high-APRI subgroup (63.79% (37/58)) had higher CVR rates than the high-HBV DNA (7.84% (4/51)) and low-APRI subgroup (28% (14/50)) respectively. High HBV DNA and low ALT patients in NG had a CVR of 0% (0/18). Cox regression identified baseline ALT ≤ 30 U/L (males) or ALT ≤ 19 U/L (females), HBV DNA > 7.21 Log10 IU/mL, HBeAg positive state, APRI < 0.32, and a decrease in HBV DNA < 3.49 Log10 IU/mL at 12 weeks as independent adverse predictors of CVR.ConclusionThe NG group has lower CVR, but the high-normal ALT subgroup performs similarly to MAG. High HBV DNA and low ALT significantly reduce CVR. Key adverse predictors include low ALT, high HBV DNA, HBeAg positivity, low APRI, and suboptimal viral reduction at 12 weeks.